2021
DOI: 10.3346/jkms.2021.36.e219
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Triptorelin 3-Month Depot Compared to 1-Month Depot for the Treatment of Korean Girls with Central Precocious Puberty in Single Tertiary Center

Abstract: Background Triptorelin depot is largely used to treat central precocious puberty (CPP) in children, and a 3-month depot has been introduced. However, data about the 3-month gonadotropin-releasing hormone use for treatment of CPP in Korean girls are not available. This study was conducted to compare the efficacy of a triptorelin 11.25 mg 3-month depot with that of a 3.75 mg 1-month depot in suppressing pubertal development for the treatment of CPP. Methods A retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Tere is still controversy over the appropriate LH suppression cut-of value with GnRHa stimulation [26][27][28]. In our study, we used LH < 2.5 IU/L as the cut-of value for LH suppression, which is consistent with previous studies [14]. Tere was no signifcant diference in suppression of LH between the two groups, and serum LH and serum E2 concentrations declined approximately 7-10-fold from baseline to 6 months after treatment.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Tere is still controversy over the appropriate LH suppression cut-of value with GnRHa stimulation [26][27][28]. In our study, we used LH < 2.5 IU/L as the cut-of value for LH suppression, which is consistent with previous studies [14]. Tere was no signifcant diference in suppression of LH between the two groups, and serum LH and serum E2 concentrations declined approximately 7-10-fold from baseline to 6 months after treatment.…”
Section: Discussionsupporting
confidence: 77%
“…Our results showed that LA 3-month depots were similarly effective to LA 1-month depots. Although our study is a single center, short-term study, we have seen the report of Chung et al [ 14 ] from Chorea, which is larger and have a longer follow-up period. They found that a suppressed levels of LH was seen in 93.5% and 100% of the girls treated with the 3-month and 1-month depots after 1 year of treatment, respectively ( P =0.226).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The 6-mo TP formulation recently approved for CPP offers greater convenience to children than other formulations, by reducing the injection frequency; however, related research is very limited (12). The 1-month dose presentation is still the most used, and usage of the 3-month dosage form is increasing (32)(33)(34); however, there is a lack of clinical experience worldwide regarding the use of the 6-month formulation (35). It has not yet been universalized, and doubts about its efficacy and safety persist among guardians and pediatric endocrinologists (1,35).…”
Section: Discussionmentioning
confidence: 99%